Characteristics of linear alternator performance under thermoacoustic-power-conversion conditions - Ibrahim, Ahmed (AUC Knowledge Fountain, 2019)
Recently, immense research work was done on the thermoacoustics power converters for their great potential in generating electricity by different types of heat sources, including solar energy, waste heat as well as conventional fuels. This work studies the performance of the linear alternator which is the part responsible for converting the acoustic power generated by the thermoacoustic engine into electric power. This work encompasses three parts: the first part is an analytical model that consists of algebraic equations that estimate the main acoustic, mechanical and electrical performance indices of the linear alternator and the relationships between them under linear loading case. These equations are experimentally validated under different conditions. These equations are used to analyze the effects of the operation conditions such as operation under mechanical resonance and electrical resonance, the values of linear alternator parameters and the load parameters on the performance of the linear alternator. This part of work introduces the relationship between the effective inductance of the linear alternator and the mechanical stroke. Additionally, this part introduces an optimization for the piston area to achieve the minimum sum of the mechanical motion loss and the Ohmic loss and an optimization for the load resistance to achieve the maximum electric power in the load and to achieve the maximum acoustic-to-electric conversion efficiency. The second part of this work is an experimental parametric study using an experimental setup that was built for testing the linear alternator over a wide range of the thermoacoustic-power-conversion conditions that cannot be experimentally achieved in the case of testing the linear alternator with thermoacoustic engine. The parametric study covers the performance of the linear alternator under linear loading case and non-linear loading case. The effects of operating frequency, input dynamic pressure ratio, mean gas pressure, gas mixture, electric load value and the value of the power-factor-correcting capacitor on the performance indices are studied under the two types of loads. The results of the parametric study in the linear load case are compared to results of the analytical model and DELTAEC simulations and good agreement was found. The third part of this work is a sensitivity analysis that utilizes design-of-experiment methodology to estimate how the factors and their combined interactions affect the performance indices of the linear alternator under linear loading. The results of the study build a comprehensive study about the linear alternator performance under thermoacoustic-power-conversion conditions. The result are useful to properly select a linear alternator for an existing engine, or vice versa and to match the resulting system to an electric load. The results can be used to select the operating conditions that result in large generted power and or large efficiency. The results can be used to control the operating conditions in the correct proportions to achieve a certain required performance index, while observing the effects on other indices.